Digit ratio, color polymorphism and egg testosterone in the Australian painted dragon. - Michael Tobler (Public Library of Science (PLoS), 2011)
Variation in exposure to sex hormones during early development contributes to phenotypic plasticity in vertebrate offspring. As a proposed marker for prenatal sex hormone exposure and because of their association with various physiological and behavioral characteristics, digit ratio and/or digit length have received notable interest within the field of evolutionary ecology. However, the validity of digit measures as a proxy of prenatal sex hormone exposure is controversial and only few studies have provided direct evidence for the link between digit development and prenatal sex hormones. Here, we report morph- and sex-specific variation in digit ratio in wild painted dragon lizards (Ctenophorus pictus). Lizards expressing a yellow bib have significantly larger third-to-fourth toe ratios (3D:4D) than lizards without a bib. Males have significantly smaller 3D:4D than females. Furthermore, we show that experimental elevation of yolk testosterone significantly increases 3D:4D in hatchling painted dragon lizards, but has no influence on hatchling size. Our results provide direct and indirect evidence for the involvement of prenatal sex steroids in digit development and it is suggested that digit ratio may be used as a biomarker for prenatal steroid exposure in this reptilian species. As such, digit ratio may provide a useful tool to study temporal or spatial differences in the proximate hormonal mechanisms modulating physiological and behavioural phenotypes.